ECONOMIC HISTORY — SCIENCE AND ACADEMIC DISCIPLINE On the 5-th anniversary of foundation of the Department „Economic History and History of Economic Thought” Financial University under the Government of the Russian Federation - I. N. Shapkin; N. O. Voskresenskaya (Финансы: теория и практика)
Economic history as a science performs a number of important tasks. It is engaged in the systematization and analysis of factual historical-economic material to justify economic theory, performs a predictive function, which explores the regularities of economic development of society, the experience of economic reforms and implementation of economic policy of countries in specific historical periods. Economic history gives the opportunity to see long-term trends of economic development. As an academic discipline it is one of the basic courses of modern economic and managerial education.